Analysis of fifth-grade students' numeracy literacy skills in Mathematics - Melinda Rahmah; Zulfadewina Zulfadewina (Universitas Pendidikan Indonesia, 2025)
The study's background highlights the low level of numeracy literacy among students in Indonesia, which limits their ability to perform calculations in everyday life. This study aims to examine the factors that influence numeracy literacy in Mathematics learning, particularly in fractions, and to analyze teachers' efforts to improve their skills. The research method is qualitative, with data collection techniques including observation, interviews, document review, and tests. The research participants included the principal, fifth-grade teachers, and fifth-grade students. The results indicated that students' literacy skills were in the moderate range, with indicators of communication and representation still requiring improvement. Numeracy skills were in the fairly good category, particularly in procedural aspects. However, difficulties remained in selecting strategies for solving fractions with different denominators. Teachers have made efforts to improve by using visual media, contextual questions, and group discussions, although limited resources and a narrow range of methods remain the primary obstacles. It can be concluded that students' literacy and numeracy skills have developed, but still require practice and innovation in learning strategies to support the achievement of the Kurikulum Merdeka competencies. Abstrak Latar belakang penelitian menyoroti rendahnya kemampuan literasi numerasi murid di Indonesia sehingga memengaruhi praktik berhitung dalam kehidupan sehari-hari. Penelitian ini bertujuan untuk untuk mengkaji faktor yang mempengaruhi kemampuan literasi numerasi pada pembelajaran Matematika, khususnya materi pecahan, serta menganalisis upaya guru dalam meningkatkan keterampilannya. Metode penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dokumentasi, dan tes. Partisipan penelitian meliputi kepala sekolah, guru kelas V, dan murid kelas V. Hasil penelitian menunjukkan bahwa kemampuan literasi murid berada pada kategori sedang, dengan indikator komunikasi dan representasi masih memerlukan penguatan. Kemampuan numerasi berada pada kategori cukup baik, terutama pada aspek prosedural, namun masih ditemukan kesulitan pada pemilihan strategi penyelesaian soal pecahan berbeda penyebut. Guru telah melakukan upaya peningkatan melalui penggunaan media visual, soal kontekstual, serta diskusi kelompok, meskipun keterbatasan sarana dan variasi metode menjadi kendala utama. Dapat disimpulkan bahwa kemampuan literasi dan numerasi murid sudah berkembang namun masih memerlukan pembiasaan dan inovasi strategi pembelajaran agar dapat mendukung capaian kompetensi Kurikulum Merdeka. Kata Kunci: kemampuan numerasi; literasi numerasi; pembelajaran Matematika